ANALYSIS METHODS OF WASTE WATER TREATMENT HIGH-FOOD INDUSTRY ENTERPRISES - , Г. И., А. А., С. В. (Municipal economy of cities. Series: «Economy science», 2013)
We consider the current problems of highly concentrated wastewater treatment food industry and their negative impact on the environment. Lit modern techniques and technologies used for this task.